Changes in tactical performance and self-efficacy on young female basketball players - Thiago José Leonardi; Mônica Cristina Starapoli Martins; Carlos Eduardo de Barros Gonçalves; Roberto Rodrigues Paes; Humberto Jorge Gonçalves Moreira de Carvalho (Revista Brasileira de Cineantropometria e Desempenho Humano)
The present study examined changes in tactical performance and self-efficacy among young female basketball players across a 4-months competitive season. Repeated measures pre- and post a 4-month season in 30 young female basketball players (11.4 to 14.7 years-old) was considered. We applied the Self-Efficacy General Scale and examined tactical performance in a standardized 3 vs 3 exercise in half court. The 3 vs 3 exercise was analysed using Game Performance Assessment Instrument (GPAI) and Team Sport Assessment Procedure (TSAP). We examined changes in tactical performance and self-efficacy using multilevel modelling. The results showed that changes of Self-Efficacy scores were not influenced by 4 months of training across competition period, chronological age and years of sport participation, the changes of TSAP performance was influenced only by years of sport participation, and the changes of GPAI performance was influenced only by the period of training and competition games.